The cytokine-serum amyloid A-chemokine network. (August 2016) - De Buck, Mieke; Gouwy, Mieke; Wang, Ji Ming; Van Snick, Jacques; Proost, Paul; Struyf, Sofie; Van Damme, Jo
Highlights: Cytokines are potent inducers of serum amyloid A (SAA) in hepatocytes. SAA induces several cytokines and chemokines, mediating its biological functions. SAA induces chemokines via TLR2 whereas it directly chemoattracts leukocytes via FPR2. SAA synergizes with induced chemokines to enhance leukocyte migration. A cytokine-SAA-chemokine cascade is established during inflammation Abstract: Levels of serum amyloid A (SAA), a major acute phase protein in humans, are increased up to 1000-fold upon infection, trauma, cancer or other inflammatory events. However, the exact role of SAA in host defense is yet not fully understood. Several pro- and anti-inflammatory properties have been ascribed to SAA. Here, the regulated production of SAA by cytokines and glucocorticoids is discussed first. Secondly, the cytokine and chemokine inducing capacity of SAA and its receptor usage are reviewed. Thirdly, the direct (via FPR2) and indirect (via TLR2) chemotactic effects of SAA and its synergy with chemokines are unraveled. Altogether, a complex cytokine–SAA–chemokine network is established, in which SAA plays a key role in regulating the inflammatory response.